2023
DOI: 10.14744/tjtes.2023.22780
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of early rehabilitation in hand burns

Sevgi Kara

Abstract: BACKGROUND:Hand burn trauma occurs quite commonly and the outcome of hand burns can significantly impact self-care daily function, work and employment, leisure activities, and overall health-related quality of life. The overall goal of the management of hand burn trauma is to optimize hand function. Rehabilitation and restoration of hand function are critical for the patient's independence and re-integration into society and work. The purpose of this study is to present our experience with 105 hand burn trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
(35 reference statements)
0
7
0
4
Order By: Relevance
“…Un programa integral de fisioterapia y terapia ocupacional es esencial para ayudar a los pacientes a recuperar su función óptima después de un traumatismo por quemadura en la mano y a reintegrarse a la vida social y laboral. La terapia es más beneficiosa cuando se inicia en el momento del ingreso y puede ser durante semanas o meses después del alta (16).…”
Section: Intervención Fisioterapéuticaunclassified
See 2 more Smart Citations
“…Un programa integral de fisioterapia y terapia ocupacional es esencial para ayudar a los pacientes a recuperar su función óptima después de un traumatismo por quemadura en la mano y a reintegrarse a la vida social y laboral. La terapia es más beneficiosa cuando se inicia en el momento del ingreso y puede ser durante semanas o meses después del alta (16).…”
Section: Intervención Fisioterapéuticaunclassified
“…Los primeros objetivos en el tratamiento de quemaduras deben ser ayudar a disminuir el edema y el dolor, mantener la fuerza muscular, aumentar el rango de movimiento con la movilidad articular y prevenir el desarrollo de contracturas yo tras deformidades (16). Es evidente que para cumplir con los objetivos mencionados se debe valorar al paciente, y conocer sus antecedentes para prescribir un plan de tratamiento en fisioterapia de acuerdo con la zona afectada la profundidad y porcentaje de quemadura y limitaciones de movimiento y dolor del paciente.…”
Section: Wwwanatomiadigitalorgunclassified
See 1 more Smart Citation
“…Consequently, hand burns are particularly predisposed to diminished functionality [ 15 , 16 ]. However, known factors that mitigate the negative effects and improve rehabilitation include an early initiation of intensive exercise and physiotherapy [ 17 , 18 ]. Several studies have demonstrated that individuals with hand burns experience the most improvement three months after the burn incident with the implementation of physiotherapy [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extension of the wrists experienced a notable reduction in range of motion (ROM) within a 12month period [9]. Therefore, the main emphasis of rehabilitation endeavors lies in preventing the loss of ROM in extension [9,10].…”
Section: Introductionmentioning
confidence: 99%